Effects of phenobarbital on serum and liver paraoxonase and arylesterase activities in rats - Atessahin, A; Karahan, I; Pirinçci, I; Gürsu, MF; Gülcü, F (Scientific Technical Research Council Turkey, 2004)
This study was carried out to determine the effects of phenobarbital, administered orally and intraperitoneally over different periods, on paraoxonase, arylesterase, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities and total protein levels in the serum and liver. Thirty-six rats, 16-18 weeks old and weighing 240-260 g, were used. Phenobarbital was applied both orally and intraperitoneally at a dose of 100 mg/kg. Paraoxonase and arylesterase activities in serum and liver samples were measured spectrophotometrically using paraoxon and phenylasetate substrates, respectively. Although no significant changes were determined in serum paraoxonase and arylesterase activities, liver paraoxonase and arylesterase activities and total protein levels increased significantly in both the orally and intraperitoneally treated groups. An increase was observed in serum ALT and AST activities, which may indicate the presence of liver damage. In conclusion phenobarbital, known as a classical enzyme inducer, may increase the activities of the aforementioned enzymes by increasing the synthesis of new proteins in liver microsomes.
Keywords: rat; pherobarbital; paraoxonase; arylesterase